Investigating Teachers’ Beliefs about Language Awareness in EFL Context in Indonesia - Ria Nur Apriyani (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2022)
This research provides an in-depth investigation into the views of teachers beliefs’ a language knowledge approach to foreign language education in secondary school. The goal of the study is to deepen our understanding of the differences in the views of teachers on language awareness and to encourage debate on the inclusion of language awareness in foreign language curricula. Two EFL teachers have been interviewed about their language awareness values. Review of the interviews found that teachers do not have a common understanding of the notion of language awareness. The findings suggest a range of issues that need to be tackled when integrating language knowledge into the education of foreign languages. These problems could serve as a starting point for a conversation with teachers and between them. In addition, teachers should be motivated to figure out how language knowledge works best within the new EFL curriculum.